2020
DOI: 10.3389/fmicb.2020.00119
|View full text |Cite
|
Sign up to set email alerts
|

Feed Additives Differentially Impact the Epimural Microbiota and Host Epithelial Gene Expression of the Bovine Rumen Fed Diets Rich in Concentrates

Abstract: Petri et al. Feed Additives Impact Epimural Ecosystem highest positive Pearson correlations to biogenic amines tested in the rumen fluid including putrescine (r = 0.67), cadaverine (r = 0.84), and tyramine (r = 0.83). These results show that supplementing feed additives to high grain diets can have a positive influence on the stability of the epimural populations, and that changes in the epimural community are correlated with changes in host epithelial gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…These included projects conducted in Austria [9,10,[17][18][19][20], the USA [21,22], Ireland (unpublished; PRJNA484585), Belgium [23], and Germany [24]. Studies conducted in Austria [9,10], [17][18][19][20] were all conducted at the same farm and in some cases using the same animals. Two studies conducted in the USA were conducted in different farms [21,22].…”
Section: Datasetsmentioning
confidence: 99%
See 3 more Smart Citations
“…These included projects conducted in Austria [9,10,[17][18][19][20], the USA [21,22], Ireland (unpublished; PRJNA484585), Belgium [23], and Germany [24]. Studies conducted in Austria [9,10], [17][18][19][20] were all conducted at the same farm and in some cases using the same animals. Two studies conducted in the USA were conducted in different farms [21,22].…”
Section: Datasetsmentioning
confidence: 99%
“…All projects included purebred Holstein-Friesian dairy cows, with the exception of the study from Ireland which used Holstein and Charolais steers (unpublished; PRJNA484585). Biopsy samples were collected from several locations: ventral sac [9,10,[17][18][19][20][21]23,24], (unpublished; PRJNA484585), dorsal sac [22], cranial sac [21], caudoventral blind sac [21], and caudodorsal blind sac [21]. All studies used primers sets for Illumina paired-end sequencing of the V4 [21,22,24], V3-4 [23], and V3-5 [9,10,[17][18][19][20] hypervariable regions (Table 2).…”
Section: Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, diets with high energy and protein levels in Group H effectively promoted the growth performance and carcass characteristics of goats. Meanwhile, the digestion and absorption of these diets were closely related to the rumen bacteria [40][41][42]. A previous study reported that the changes in the ruminal microbiota could help promote the ADG of goats [5].…”
Section: Comparison Of the Composition And Differences Of Ruminal Bacmentioning
confidence: 98%